Purification and Characterization of Pectinase from Bacillus licheniformis obtained from a Cassava Waste Dump - Madu, Joshua Osuigwe; Okonji, Raphael Emuebie; Torimiro, Nkem; Agboola, Femi Kayode (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
This study investigated the properties of pectinase from Bacillus licheniformis. The pectinase secreted by the microorganism was purified using ion exchange and gel filtration chromatography on DEAE-Sephadex and Sephadex G-200 respectively. A purification fold of 10.5, yield of 23.9% and specific activity of 9.47 U/mg was obtained. The characteristics of the enzyme included a native molecular weight of 38 kDa, pH optimum 9.0, temperature stability between 35 and 45ºC; temperature optimum 50°C. Inhibition of the enzyme was observed with metal and chemicals, such as Ba2+, Al3+, Mg2+, EDTA, benzoic acid, tannic acid, citric acid and sodium oxalate, however the enzyme activity was enhanced in the presence of K+ and Na+. Other enzymatic properties was Km values of 1.37, 1.62, and 9.09 mg/ml for polygalacturonic acid, 7.8% methylated pectin and 67% methylated pectin respectively The pectinase produced have some desirable characteristics that could be utilised in many industrial processes.